The Effect of Financial Literature on Financial Behavior in The Mediation of Financial Knowledge on Student of The Faculty of Economics and Business Muhammadiyah University - Muslih Muslih; Trifa Maylani (Management Department Universitas Islam Negeri Sumatera Utara, 2021)
This study aimed to determine and analyze the effect of Financial Literacy on Financial Behavior mediated by Financial Knowledge on Students of the Faculty of Economics and Business, University of Muhammadiyah North Sumatra. The method used in this study is to use the associative approach and survey methods. The population was students of the Faculty of Economics and Business, University of Muhammadiyah North Sumatra, with 4158 students. The number of samples used in this study amounted to 88 people using non-probability sampling, an accidental sampling technique with the criteria for the concentration of financial management students in 2017 and 2018. The data collection techniques used in this study used interview techniques and questionnaires/questionnaires. The data analysis technique in this study used descriptive statistical analysis and path analysis with partial least squares (PLS). Data processing in this study using the Smart PLS 3 Software program. The results of this study indicate that financial literacy has a positive and significant effect on financial behavior in students of the Faculty of Economics and Business, University of Muhammadiyah, North Sumatra. Financial literacy positively and significantly affects Financial Knowledge in the Faculty of Economics and Business University of Muhammadiyah North Sumatra students.Keyword: Financial behavior, financial literacy, financial knowledge